Linguistic Features of Uzbek and English News Writing - Rahimov, G’anisher (ANGLISTICUM. Journal of the Association-Institute for English Language and American Studies, 2017)
Of all the countless genres of written communication made available to us in our daily lives, news-related articles are among the most important. The purpose of this article is to provide topically relevant and interesting information to the public in a clear, reader-friendly manner, explicitly focusing on the main facts and details about the people, places, and events targeted in the reports. As such, certain grammatical generalizations can be made about the genre of news writing. For example, news articles often contain more noun phrases than verb phrases compared to genres of spoken communication and even other genres of written communication (Biber, Johansson, Leech, Conrad & Finegan, 1999). Keywords: news writing, Uzbek news, US news, lexical features, grammatical features, articles, etc.